Why accountants should embrace machine learning? - LEE, Benjamin Huan Zhou (Institutional Knowledge at Singapore Management University, 2018)
AI and ML are enabling tools that take the tedious gruntwork out of accounting, freeing up professionals to provide valuable insights - as well as professional scepticism - which are sought-after services no machine can replicate.